The Controversy of Siyahi Marriage: A Maqasid Shariah Perspective and Its Relevance in Indonesia - Abdur Rahman Adi Saputera (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2024)
The phenomenon of Nikah Siyahi, or temporary marriage during travel, has become a controversial topic in Islamic law. This practice is often carried out by Muslim travelers to enjoy sexual relations without violating religious principles. However, scholars have diverse opinions regarding Nikah Siyahi. Some endorse it as an alternative to avoiding zina (fornication), while others reject it for undermining fundamental values of marriage, such as commitment and purity. This study aims to explore Islamic legal perspectives on Nikah Siyahi and analyze the impacts of this practice through the lens of Maqasid Shariah, which are the primary principles of Islamic law intended to protect religion, life, lineage, property, and intellect. The research employs a library research method to gather views from various literatures on Islamic law. Although it may formally meet the requirements of Islamic marriage, Nikah Siyahi fundamentally contradicts the ideal objectives of marriage in Islam. From the perspective of Maqasid Shariah, this practice can have negative repercussions on the dignity of religion, mental health, family stability, and the rights of offspring. In Indonesia, where marriage law is clearly regulated, this practice brings more harm than benefit. Therefore, the enforcement of law and community education regarding the essence of marriage in Islam must be strengthened to protect fundamental values of Shariah